Peran Dosen dalam Mengatasi Kesulitan Membaca Al-Quran pada Mahasiswa UIN RIL - Evi Febriani; Muhamad Kumaidi; Muhamad Anas Ghofur (Departement of Mathematics Education, 2024)
This research aims to elucidate the crucial role of lecturers in helping students overcome difficulties in understanding and reading the Qur'an at UIN RIL. Lecturers serve not only as providers of knowledge but also as mentors and supporters for students in the learning process. The study employs a qualitative descriptive approach through interviews and observations of lecturers and students. Findings indicate that lecturers play a pivotal role through personalized approaches, learning evaluations, and interactive material provision, effectively addressing student challenges. A descriptive qualitative method is utilized to generate data describing the social situation in the field, with analyses yielding conclusions that complement quantitative findings.